Genetic Analyses of Wheat and Molecular Marker-Assisted Breeding, Volume 2 Conditional QTL Analysis and MAS - Tian, Jichun; Chen, Jiansheng; Chen, Guangfeng; Wu, Peng; Zhang, Han; Zhao, Yong (Springer Netherlands : Imprint: Springer, 2015)
While focusing on various interactions between trait genes/QTL and dynamic expressions of conditional QTL genes, this book also discusses aspects of molecular marker-assisted breeding, and applications of molecular markers associated with yield, quality, physiology and disease resistance in wheat. It covers QTL studies in wheat breeding and presents the available information on wheat MAS breeding. This volume provides a wealth of novel information, a wide range of applications and deep insights into crop genetics and molecular breeding, which is valuable not only for plant breeders but also for academic faculties, senior researchers and advanced graduate students who are involved in plant breeding and genetics. Dr. Jichun Tian is a professor at the Department of Agronomy, Shandong Agricultural University, Tai'an, China.